Characteristics and management of dental implants displaced into the maxillary sinus: a systematic review. Issue 2 (February 2023) - Seigneur, M.; Hascoët, E.; Chaux, A.-G.; Lesclous, P.; Hoornaert, A.; Cloitre, A.
Abstract: The displacement of dental implants into the maxillary sinus is increasingly reported and may lead to serious complications. Better knowledge of this condition could help clinicians improve their practice, but it is difficult to draw conclusions from the current literature. Therefore, a systematic review was performed to describe the main characteristics of dental implant displacement, as well as its management and temporal evolution over a 31-year period. This review was conducted according to the PRISMA methodology. The PubMed/Scopus electronic databases were searched to December 2021. Risk of bias was assessed using the Joanna Briggs Institute tools. A total of 73 articles reporting 321 patients with displaced dental implants were included. Implants located in the upper first molar site were the most frequently involved (23.7%). Displacement occurred mainly during the first 6 months after implant placement (62.6%). The majority became symptomatic (56.2%), most often due to maxillary sinusitis and/or oroantral communication (44.2%). The surgical approaches to remove displaced implants were the lateral approach (38.1%), the Caldwell–Luc approach (27.2%), and endoscopic nasal surgery (23.1%). This review highlights the importance of preventive measures: avoiding implant displacement by careful pre-implantation radiographic analysis, but also preventing infectious complications through early removal of the displaced implant (PROSPERO CRD42021279473).